Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Guru SMA N 1 Pamotan - Hidayat, Moh Asif Nur; Dewi, Dian Ayu Liana (Manajemen & Bisnis Jurnal, 2024)
The objective of this study is to illustrate and rationalize the impact of work discipline and motivation on the performance of teachers in SMA N 1 Pamotan school. With a total of 47 teachers as respondents, this study used qualitative methods. Sampling techniques use saturated samples. Multiple linear regression analysis approaches are used in data analysis methods. The resullts showeed the teachers’ performance in SMA N 1 Pamotan school were significantly better because of work discipline and significantly worse because they were heavily motivated. The resultts of this studdy indicate that the implementation of dicipline strict work has a signifficant impactt on the effectiveness of teachers in schools located in SMA N 1 Pamotaan Province. SMA N 1 Pamotan school teachers exhibit a high level of poor performance when it comes to work motivatiion